2019
DOI: 10.1080/10408444.2019.1621263
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A co-exposure effects: a key factor in understanding BPA’s complex mechanism and health outcomes

Abstract: Bisphenol A (BPA) is an environmental endocrine disrupting chemical widely used in the production of consumer products, such as polycarbonate plastics, epoxies and thermal receipt paper. Human exposure to BPA is ubiquitous due to its high-volume production and use. BPA exposure has been associated with obesity, diabetes, reproductive disorders and cancer. Yet, the molecular mechanisms or modes of action underlying these disease outcomes are poorly understood due to the pleiotropic effects induced by BPA. A fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 114 publications
(184 reference statements)
3
24
0
1
Order By: Relevance
“…Thus, concern regarding whether BPA exposure causes brain health problems in humans has grown. Reliable evidence supports the supposition that BPA impairs brain development (e.g., neural stem cell proliferation and differentiation) and induces neurodegeneration [2,5,6,37]. Herein, we demonstrated that BPA is directly toxic to differentiating N2a neurons, leading to insults including AIF-dependent apoptosis and impaired autophagy flux.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, concern regarding whether BPA exposure causes brain health problems in humans has grown. Reliable evidence supports the supposition that BPA impairs brain development (e.g., neural stem cell proliferation and differentiation) and induces neurodegeneration [2,5,6,37]. Herein, we demonstrated that BPA is directly toxic to differentiating N2a neurons, leading to insults including AIF-dependent apoptosis and impaired autophagy flux.…”
Section: Discussionsupporting
confidence: 74%
“…Bisphenol A (BPA) is a common endocrine-disrupting chemical widely used in the manufacture of polycarbonate plastics and epoxy resins, and people inevitably come into contact with it in daily life [1][2][3][4]. Growing evidence suggests close correlations between BPA exposure, pathogenetic brain degeneration (e.g., Alzheimer's disease (AD)), and altered neurobehaviors (e.g., cognitive decline) [5,6], which implies that BPA is an emerging risk factor for cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, however, adolescent exposure to BPA inhibited hops-induced open arm entries in co-exposed rats. This co-exposure effect in regulating behavioral response substantiates a number of studies that have reported the ability of various dietary/naturally occurring compounds to regulate different BPA genomic and biochemical effects upon co-exposure at physiological and pharmacological dose regimens (Sonavane and Gassman, 2019). Interestingly, the behavioral trends observed in the EPM are concordant with BPA-induced anxiety reported at other developmental stages (Matsuda et al, 2012;Patisaul et al, 2012;Diaz Weinstein et al, 2013;Xu et al, 2015).…”
Section: Anxiety- Depressive-like Behavior and Basal Cort Secretionsupporting
confidence: 83%
“…However, combined exposure to these pollutants has not been studied thus far. Recently, a review highlighted the importance of BPA co-exposure studies with other chemicals and environmental stressors for the assessment of outcomes that common co-exposures can exert on human health [52]. Considering their simultaneous presence in the environment, exposure to mixtures of different pollutants is the only realistic exposure scenario.…”
Section: Introductionmentioning
confidence: 99%